Hypertrophic Scar Improvement by Early Intervention With Ablative Fractional Carbon Dioxide Laser Treatment. Issue 4 (16th July 2020) - Tan, Jianglin; Zhou, Junyi; Huang, Ling; Fu, Qingqing; Ao, Ming; Yuan, Lili; Luo, Gaoxing
Abstract : Background and Objectives: Ablative fractional laser treatment has been used to improve the color and texture of hypertrophic scars with safe and effective results. However, no consensus on the optimal time to initiate fractional laser treatment is available. The effect on early‐stage scars remains controversial. This study was designed to assess the efficacy and safety of ablative fractional carbon dioxide (CO2 ) laser treatments for hypertrophic burn scars and to analyze the efficacy and safety in the early period within 3 months after injury. Study Design/Materials and Methods: We performed a retrospective study of 221 hypertrophic scar patients. According to the time of the first laser treatment after injury, patients were divided into five subgroups, including less than 1 month, 1–3 months, 3–6 months, 6–12 months, and more than 12 months postinjury. One month after the last laser treatment, the scars were assessed by photography, the Vancouver Scar Scale (VSS), durometry, and spectrocolorimetry. Results: The patients included 118 males and 103 females. The average age was 33.6 years. Fire/flame was the primary injury source. Thirty‐six percent of the patients underwent at least one fractional CO2 laser treatment. All the included patients, including those treated within 1 month after injury, had significantly decreased VSS scores after laser treatment. We also noted that hardness and redness scores were decreased after treatment for both scars treated within 3 months and those treated more than 12 months after injury. Seepage (17.6%), bleeding (22.2%), and swelling (9.0%) were the main adverse events after laser treatment. Conclusions: This study demonstrated the safety and efficacy of ablative fractional CO2 laser treatment applied to early‐stage burn scars. The optimal time for laser application for burn patients can be within 1 month after injury. Durometry and spectrocolorimetry were effective for assessing scars as objective modalities. Lasers Surg. Med. © 2020 Wiley Periodicals LLC